Avaliação clínica de um novo dentifrício na redução dos compostos sulfurados voláteis - Guaitolini, Roberto Luiz (2009)
Halitosis is a problem caused in the vast majority of cases in the oral cavity and has as its main contributor to volatile sulfur compounds (VSC), which are formed from the break of amino acids by oral bacteria. The aim of this study is to assess the ability of toothpaste containing chlorine dioxide to reduce VSC levels. The study consisted of an evaluation randomized, double-blind, crossover, and placebo-controlled of 9 healthy volunteers, where the halitosis was induced through the rinse of L-cysteine (6mm - pH 7.2). Three toothpastes were used as a solution to rinse, a test (containing 0.3% cetylpyridinium chloride, 0.44% chlorine dioxide and 0.33% of sodium fluoride (NaF)), placebo (negative control) and digluconate chlorhexidine to 0.12% (positive control). Halimeter® (Halimeter ®, Interscan Corp.., Chatsworth, CA, USA) was used to measure the levels of VSC. For each toothpaste 6 measurements were made on participants: initial, post-cysteine, post-rinse, after 1 hour, after 2 hours, after 3 hours. All participants used the three different dentifrices, and had a minimum washout period of at least fifteen days between each study phase. Reduction rate means in VSC levels were calculated for each group subtracting post-cysteine values by the post-rinse values, and then normalized. Data analysis was done using Kruskal-Wallis and Student-Newman-Keuls tests and the -level was set at 0.05. The test product showed higher reduction rate in VSC levels immediately after the rinse, after 1 hour, after 2 hours and after 3 hours, when compared with placebo (p<0,05). In the period after 1 hour, after 2 hours and after 3 hours the reduction rate of test toothpaste was similar to chlorhexidine, both being statistically superior to placebo. In the period immediately after the rinse there is statistical difference between all solutions, with chlorhexidine showed higher reduction rate. Based on the results we can conclude that the toothpaste test based on chlorine dioxide was able to reduce levels of volatile sulfur compounds, are behaving in a manner similar to the solution of the 0.12% chlorhexidine after 1 hour, after 2 hours and 3 hours to rinse.